(untitled) (IITM Journal of Business Studies, 2025)
This paper addresses the concept of Search Engine Optimization (SEO), which is essential in increasing the exposure of a website and consequently making it more visible to users. SEO efforts are grouped as on-page, off-page, and technical SEO. On-page SEO includes optimizing the content, adding title, meta, and image tags, and adjusting the URLs of target websites. Promoting domain authority through backlinking, competitor analysis, and link-building strategies is called off-page SEO. Technical SEO is all about enhancing mobile accessibility, XML sitemap, robots. txt, and the security of a website so that search engines can crawl and index it more effectively. In order to capture the attention of search engines, optimizers must be well-versed in its algorithm ranking factors and ensure that the page aims to answer a user’s inquiry as well as target certain phrases that assist with higher ranking. There is an emphasis on the need for ethical SEO, and optimizers need to keep adapting to new algorithm updates if they want to remain competitive. The discussion of future perspectives raises the introduction of voice search and AI to digital marketing, which encourages pursuing deeper research.